2016
DOI: 10.1128/aem.01106-16
|View full text |Cite
|
Sign up to set email alerts
|

Ammonia as an In Situ Sanitizer: Influence of Virus Genome Type on Inactivation

Abstract: Treatment. DNA and dsRNA viruses were considerably more resistant than ssRNA viruses, resulting in up to 1,000-fold-longer treatment times to reach a 4-log inactivation. The apparently slower inactivation of DNA viruses was rationalized by the higher stability of DNA than that of ssRNA in HEAM. Pushing the system toward harsher pH (>9) and temperature (>35°C) conditions, such as those encountered in thermophilic digestion and alkaline treatments, led to more consistent inactivation kinetics among ssRNA and oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(51 citation statements)
references
References 107 publications
2
49
0
Order By: Relevance
“…Inactivation kinetics were assessed in a subset of stored urine, sludge and manure samples at 35°C, and were compared to those obtained in laboratory solution with and without NH 3 . 15,16 As expected, the ssRNA virus MS2 was inactivated more readily than the DNA viruses in most matrices, ( Fig. 1 and ESI † Table S2).…”
Section: Influence Of Genome Type and Microbial Activity On Virus Inasupporting
confidence: 75%
See 3 more Smart Citations
“…Inactivation kinetics were assessed in a subset of stored urine, sludge and manure samples at 35°C, and were compared to those obtained in laboratory solution with and without NH 3 . 15,16 As expected, the ssRNA virus MS2 was inactivated more readily than the DNA viruses in most matrices, ( Fig. 1 and ESI † Table S2).…”
Section: Influence Of Genome Type and Microbial Activity On Virus Inasupporting
confidence: 75%
“…This ability of the model to accurately predict MS2 inactivation supports the notion that the dominant underlying mechanism of inactivation is basecatalyzed transesterification of the ssRNA genome. 15,16 This appears to be the case in both synthetic solutions and in real matrices such as stored urine, and sludge and manure. Consistent with our results, Gao et al 31 recently reported that during mesophilic anaerobic treatment of Coxsackievirus, the viral genome was the main inactivating target.…”
Section: Validation Of Ms2 Inactivation Prediction In Stored Urine Smentioning
confidence: 99%
See 2 more Smart Citations
“…Doublestranded RNA and both single-and double-stranded DNA have a higher resistance to inactivation from exposure to high concentrations of ammonia with respect to single-stranded RNA, most likely because of higher stability with respect to its genomes (Decrey et al 2016, Decrey et al 2015.…”
Section: Contaminantsmentioning
confidence: 99%